Maqashid Al Syariah dalam ekonomi kontemporer negara Indonesia - Nurbaiti, Talitha Azmi; Rahmayanti, Vira; Mu'is, Ahmad (Maliki Interdisciplinary Journal, 2025)
In the framework of analyzing the meaning of Maqashid al-Syariah, this concept emphasizes the importance of justice and balance in the application of Islamic law. Islamic law is not merely a collection of written rules; behind its provisions lies a profound philosophical foundation aimed at creating a just and balanced life for humanity. The law revealed by Allah SWT has the purpose of bringing benefit to the community, making it dynamic and based on universal values that can respond to changing human needs. Maqashid al-Syariah has become a primary focus for scholars and Islamic legal experts, especially in the context of Ushul Fiqh and the methods of legal determination. This research employs a qualitative approach with library research methods to examine the applicability of Maqashid al-Syariah in contemporary Indonesian economics. The findings indicate that the application of Maqashid al-Syariah is not limited to legal aspects but also encompasses moral, social, and spiritual dimensions, striving to ensure justice and social welfare in trade practices and the banking sector. Thus, the values of Maqashid al-Syariah serve as important guidelines for creating an ethical, just, and sustainable economic system.